Acetabular reconstruction with total hip replacement and femoral head autograft following pelvic resection of malignant bone tumour: A case report. (July 2022) - Prabowo, Yogi; Alhuraiby, Sammy Saleh; Putera, Guntur Utama; Canintika, Anissa Feby
Abstract: Introduction: Pelvic tumors greatly impact survival and quality of life of the patient. Reconstruction following resection of neoplasms involving the acetabulum remains one of the most challenging procedures for orthopaedic surgeons. We reported an 18-year-old female with Hodgkin's lymphoma of the left iliac wing. Presentation of case: A 18-year-old female presented left hip pain since one year before admission. Pelvis X-ray demonstrated lytic lesion on the left iliac crest with moth-eaten pattern. However, the contrast-enhanced MRI showed the true extent of the tumour which engulfed the iliac crest and extended to the anterior border of the acetabulum. The acetabulum was reconstructed using femoral head autograft and total hip replacement. At six months of follow-up, CT scan of the pelvis demonstrated no tumour. No complications occurred during 14 months of follow-up. However, the patient died 28 months post surgery. Discussion: In pelvic sarcomas, the utilization of this technique remains limited, as the complex anatomy and the bulk of tumour growth often limits the choice of what procedure can be conducted. Reconstruction techniques have also advanced, albeit difficult and laden with complications, especially when the lesion involves the acetabulum. Conclusions: The choice of implant for pelvic resection in the developing country remains challenging due to the high cost of implants. However, in cases of pelvic sarcomas, the utilization of this technique remains limited, as the complex anatomy and the bulk of tumour growth often limits the choice of what procedure can be conducted. Reconstruction techniques have also advanced, albeit difficult and laden with complications, especially when the lesion involves the acetabulum. Highlights: Reconstruction following resection of neoplasms involving the acetabulum remains one of the most challenging procedures for orthopaedic surgeons. Endoprosthetic replacement after pelvic tumour resection is associated with a high risk of complications and functional restrictions This is a report of an 18-year-old female with Hodgkin's lymphoma of the left iliac wing treated using total hip replacement and femoral head autograft pelvic resection